Odpowiedzi

2010-01-17T17:28:37+01:00
A) 7-(3-5x)=2x-(4x+3)
7-3+5x=2x-4x-3
4-5x=-2x-3
-3x=1 /:(-3)
x-=- 1/3

b) 7+3x=4x-(2x-2)
7+3x=4x-2x+2
7+3x=2x+2
x=-5

c) (3x+3)-(x-2)=12x-5


d)(2x+3)-(6-5x)=3x+7


e) 5x=2(7-2x)-(2-3x)
5x=14-4x-2+3x
5x=12-x
4x=12 /:4
x=3

f)x=1/5(1-x/2)+2(x-1)*
x=1/5-x/10+2x-2



g)2(x+2)=5(x-1)
2x+4=5x-5
-3x=1 /:(-3)
x=-1/3

h)2x+5-(4x-2)=10-x-(5x-23)
2x+5-4x+2=10-x-5x+23
-2x+7=33-6x
4x=26 /;4
x=6,5

niektórych nie jestem pewna więc nie będę robić żeby nie wprowadzać w błąd
Najlepsza Odpowiedź!
2010-01-17T17:32:00+01:00
A) 7-(3-5x)=2x-(4x+3)
7-3+5x=2x-4x-3
5x+2x=-3-4
7x=-7/:7
x=-1

b) 7+3x=4x-(2x-2)
7+3x=4x-2x+2
3x-2x=2-7
x=-5

c) (3x+3)-(x-2)=12x-5
3x+3-x+2=12x-5
-10x=-10/:(-10)
x=1

d)(2x+3)-(6-5x)=3x+7
2x+3-6+5x=3x+7
4x=7+3
4x=10/:4
x=2,5

e) 5x=2(7-2x)-(2-3x)
5x=14-4x-2+3x
5x+x=12
6x=12/:6
x=2

g)2(x+2)=5(x-1)
2x+4=5x-5
2x-5x=-5-4
-3x=-9/:(-3)
x=3

h)2x+5-(4x-2)=10-x-(5x-23)
2x+5-4x+2=10-x-5x+23
2x-4x+x+5x=23+10-5-2
4x=26/:4
x=6,5
2010-01-17T17:32:11+01:00
1. 4+5x=-2x-3
7x=1
x=-1/7
2. 7+3x=2x+2
x=-5
3. 2x+5=12x-5
10=10x
1=x
4, 7x-3=3x+7
4x=4
x=1
5,5x=12-x
6x=12
x=2
6. x=9/10

7.2x+4=5x-5
x=3
8.2x+5-4x+2=10-x-5x+23
7-2x=33-6x
4x=26
x+6,5